(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines letters in literature and literary criticism and their place in the works of the great poets Alisher Navoi, A.S. Pushkin, Gafur Gulam and N. Gumilyov. It has been revealed that letters play an important role in studying the biography of creators entering the creative laboratory and are an important source of revealing their creative and spiritual image. Literary letters serve as a valuable resource for studying not only the lives and works of writers and critics, but also the period of writing, the history, the reasons for writing, and the mysteries with all their contradictions. Therefore, in the article, some letters of Uzbek and Russian writers are studied in a comparative-typological way. Letters are one of the most concise and effective forms of human communication.